Utilizing digital payment in the rumah ide coffee - Ritonga, Mirwansyah Putra (Junal Ilmu Manajemen, 2024)
This observation aims to increase the efficiency of financial transactions, financial management, and inventory at Rumah Ide Coffee by utilizing digital payment technology. Apart from that, another aim is to provide easy payments for customers and help cafes compete in an increasingly competitive market by adopting more advanced technology. Rumah Ide Coffee has utilized digital technology to increase efficiency as a cafe business. One way Rumah Ide Coffee operates digital payments is by accepting non-cash payments. This research uses descriptive research with a qualitative approach. Researchers interviewed several informants who were Cashier employees who managed the financial sector at Rumah Ide Coffee. Rumah Ide Coffee has used digital payments well to increase efficiency and expand its customer reach. Rumah Ide Coffee can improve its customer experience and business efficiency by accepting non-cash payments.